A comprehensive review of chitosan applications in paper science and technologies. (1st June 2023) - Gal, Mostafa Rohi; Rahmaninia, Mehdi; Hubbe, Martin A.
Abstract: Using environmentally friendly biomaterials in different aspects of human life has been considered extensively. In this respect, different biomaterials have been identified and different applications have been found for them. Currently, chitosan, the well-known derivative of the second most abundant polysaccharide in the nature (i.e., chitin), has been receiving a lot of attention. This unique biomaterial can be defined as a renewable, high cationic charge density, antibacterial, biodegradable, biocompatible, non-toxic biomaterial with high compatibility with cellulose structure, where it can be used in different applications. This review takes a deep and comprehensive look at chitosan and its derivative applications in different aspects of papermaking. Graphical abstract: Unlabelled Image